Chromosome‐level genome assembly of an important pine defoliator, Dendrolimus punctatus (Lepidoptera; Lasiocampidae). (13th July 2020) - Zhang, Sufang; Shen, Sifan; Peng, Jiong; Zhou, Xin; Kong, Xiangbo; Ren, Pingping; Liu, Fu; Han, Lingling; Zhan, Shuai; Huang, Yongping; Zhang, Aibing; Zhang, Zhen
Abstract: Dendrolimus spp. are important destructive pests of conifer forests, and Dendrolimus punctatus Walker (Lepidoptera; Lasiocampidae) is the most widely distributed Dendrolimus species. During periodic outbreaks, this species is said to make "fire without smoke" because large areas of pine forest can be quickly and heavily damaged. Yet, little is known about the molecular mechanisms that underlie the unique ecological characteristics of this forest insect. Here, we combined Pacific Biosciences (PacBio) RSII single‐molecule long reads and high‐throughput chromosome conformation capture (Hi‐C) genomics‐linked reads to produce a high‐quality, chromosome‐level reference genome for D. punctatus . The final assembly was 614 Mb with contig and scaffold N50 values of 1.39 and 22.15 Mb, respectively, and 96.96% of the contigs anchored onto 30 chromosomes. Based on the prediction, this genome contained 17, 593 protein‐coding genes and 56.16% repetitive sequences. Phylogenetic analyses indicated that D. punctatus diverged from the common ancestor of Hyphantria cunea, Spodoptera litura and Thaumetopoea pityocampa  ~ 108.91 million years ago. Many gene families that were expanded in the D. punctatus genome were significantly enriched for the xenobiotic biodegradation system, especially the cytochrome P450 gene family. This high‐quality, chromosome‐level reference genome will be a valuable resource for understanding mechanisms of D. punctatus outbreak and host resistance adaption. Because this is the first Lasiocampidae insect genome to be sequenced, it also will serve as a reference for further comparative genomics.